Inscrições discursivas na narrativa de As horas nuas de Lygia Fagundes Telles - Rosa, Ismael Ferreira (2009)
This work aims at reflecting on discursive inscriptions built up in the narrative of The naked hours (TNH) by Lygia Fagundes Telles. Based on the theory of French discourse analysis, especially on studies of Michel Pêcheux and on the dialogical-polyphonic theory of Mikhail Bakhtin, we intend to enter to the field of discursivity raised up in a literary production. We propose a qualitative analytical-descriptive of interpretative character research through which, we expose a reader-look at the opacity and the dynamic of the discursive operation produced in TNH. We investigate how the different enunciative voices, in a polyphonic way, passed through and passed by interdiscourse, and its multiplicity of discursive subject, in its subject-forms, composed the discursive inscriptions, constitutive and constituent in/from the book. Thus, based on Santos (2007), we established an analytical and methodological support observing the concept of N-essence. That support consists in building associations of constituted, constitutive and constituent elements of operator-concepts. We suggest the quintessence in double-helix device, in which we mobilize an environment of a subjectmental order and other of a sensemental order to analysis the significance process in the operation of the discursive inscriptions. Combined to the cutting technique (ORLANDI, 1996), we established ten epistemic-analytical operators (five of the subjectmental order, in the 1st helix and five of the sensemental order, in the 2nd helix) to study the processes of sense construction from the discursive inscriptions cut, observing the criteria of recurrence and regularity. The analysis has shown which process is established throughout the novel: the constitution of subject-forms in the core of its discursive subscriptions and interdiscourse crossings, imbricated to intradiscourse, on a dialogical-polyphonic way. Those made them build and firm themselves like autonomous consciences. By their own voices, they meant, meaning themselves, building, therefore, past-present-future identities. It was in mirror relations reflecting verses and reverses and in otherity relations that subjects and senses were produced. Singular subjects and senses that make this novel a tellian aesthetic enunciation so interpellative and particular.